HW2 - Section 2.1 1. f (3) = 5(3) + 6 = 15 + 6 = 21 f (- 3)...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 2.1 1. f (3) = 5(3) + 6 = 15 + 6 = 21 f (- 3) = 5(- 3) + 6 =- 15 + 6 =- 9 f ( a ) = 5( a ) + 6 = 5 a + 6 f (- a ) = 5(- a ) + 6 =- 5 a + 6 f ( a + 3) = 5( a + 3) + 6 = 5 a + 15 + 6 = 5 a + 21 3. g (0) = 3(0) 2- 6(0)- 3 = 0 + 0- 3 =- 3 g (- 1) = 3(- 1) 2- 6(- 1)- 3 = 3 + 6- 3 = 6 g ( a ) = 3( a ) 2- 6( a )- 3 = 3 a 2- 6 a- 3 g (- a ) = 3(- a ) 2- 6(- a )- 3 = 3 a 2 + 6 a- 3 g ( x +1) = 3( x +1) 2- 6( x +1)- 3 = 3( x 2 +2 x +1)- 6 x- 6- 3 = 3 x 2 +6 x +3- 6 x- 6- 3 = 3 x 2- 6 5. f ( a + h ) = 2( a + h ) + 5 = 2 a + 2 h + 5 f (- a ) = 2(- a ) + 5 =- 2 a + 5 f ( a 2 ) = 2( a 2 ) + 5 = 2 a 2 + 5 f ( a- 2 h ) = 2( a- 2 h ) + 5 = 2 a- 4 h + 5 f (2 a- h ) = 2(2 a- h ) + 5 = 4 a- 2 h + 5 7. s (4) = 2(4) (4) 2- 1 = 8 16- 1 = 8 15 s (0) = 2(0) (0) 2- 1 =- 1 =- 1 = 0 s ( a ) = 2( a ) ( a ) 2- 1 = 2 a a 2- 1 s (2 + a ) = 2(2+ a ) (2+ a ) 2- 1 = 4+2 a (4+4 a + a 2 )- 1 = 4+2 a a 2 +4 a +3 s ( t + 1) = 2( t +1) ( t +1) 2- 1 = 2 t +2 ( t 2 +2 t +1)- 1 = 2 t +2 t 2 +2 t 9. f (2) = 2(2) 2 (2)- 1 = 2(4) (2)- 1 = 8 1 = 8 f ( a ) = 2( a ) 2 ( a )- 1 = 2( a 2 ) a- 1 = 2 a 2 a- 1 f ( x + 1) = 2( x +1) 2 ( x +1)- 1 = 2( x 2 +2 x +1) x +1- 1 = 2 x 2 +4 x +2 x f ( x- 1) = 2( x- 1) 2 ( x- 1)- 1 = 2( x 2- 2 x +1) x- 1- 1 = 2 x 2- 4 x +2 x- 2 11. f (- 2) = (- 2) 2 + 1 = 4 + 1 = 5 f (0) = (0) 2 + 1 = 0 + 1 = 1 f (1) = q (1) = 1 = 1 13. f (- 1) =- (1 / 2)(- 1) 2 + 3 =- (1 / 2)(1) + 3 =- (1 / 2) + 3 = (5 / 2) f (0) =- (1 / 2)(0) 2 + 3 = 0 + 3 = 3 f (1) = 2(1) 2 + 1 = 2(1) + 1 = 2 + 1 = 3 f (2) = 2(2) 2 + 1 = 2(4) + 1 = 8 + 1 = 9 15. f (0) =- 2 . f ( x ) = 3 when x = 2 and f ( x ) = 0 when x = 1 . The domain of f ( x ) is given in interval notation by [0 , 6] . The range of f ( x ) is given in interval notation by [- 2 , 6] . 17. The point (2 , 3) lies on the graph if g (2) = 3. g (2) = q (2) 2- 1 = 4- 1 = 3; so that the point is on the graph. 19. The point (- 2 ,- 3) lies on the graph if f (- 2) =- 3. f (- 2) = | (- 2)- 1 | (- 2)+1 = |- 3 |- 1 = 3- 1 =- 3; so that the point is on the graph. 21. The point (1 , 5) lies on the graph if f (1) = 5. f (1) = 2(1) 2- 4(1) + c = 2- 4 + c =- 2 + c ; setting this equal to 5 we find- 2 + c = 5 c = 7 . 23. The function f ( x ) = x 2 + 3 is a polynomial and hence defined for all x so its domain in interval notation is given by (- , ) . 25. The function f ( x ) = 3 x +1 x 2 is a rational function and hence defined for all x for which the denominator is nonzero; the denominator is zero at x = 0 so its domain in interval notation is given by (- , 0) (0 , ) . 27. The function f ( x ) = x 2 + 1 is a radical and hence is defined for all x values for which x 2 + 1 0; since this inequality is true for all x, the functions domain in interval notation is given by (- , ) ....
View Full Document

Page1 / 24

HW2 - Section 2.1 1. f (3) = 5(3) + 6 = 15 + 6 = 21 f (- 3)...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online